Peranan Layanan Kunjungan Online terhadap Kondisi Psikologis Narapidana di Lembaga Pemasyarakatan Kelas II A Purwokerto - Rizky Milenia; Herry F.B. Butar (UIN Fatmawati Sukarno Bengkulu, 2022)
Online visitation services have an effect on the psychological condition of inmates. The purpose of this study is to find out the effect it has on the psychological condition of inmates through online visitation services at Lapas Class IIA Purwokerto. The method used in this study is qualitative descriptive, which describes directly the implementation to get information about the implementation of online visiting services and their effect on the psychological condition of inmates in Lapas Class IIA Purwokerto. Data collection techniques are carried out by means of direct observation observation, in-person interviews to inmates and literature studies to increase understanding and deepening of theory. The data that has been collected will be analyzed qualitatively and then presented descriptively. The results found differences in the behavior and psychological condition of inmates who often, rarely and never make visits. Inmates who often do relatively quieter, while inmates who rarely and never behave alone and pemurung.